ANALISIS HUKUM ISLAM TENTANG TINGGINYA ANGKA PERCERAIAN DI PENGADILAN AGAMA MERAUKE TAHUN 2020 - Musyahid, Achmad; Al Qasdijal, Amran (ISTIQRA: Jurnal Hasil Penelitian, 2022)
Analysis of Islamic law regarding the high divorce rate in the working area of the Merauke Regency Religious Court shows that 1) The divorce rate in the working area of the Merauke Regency Religious Court in 2020 was 338 couples out of a total of 53,728 couples, 2) The highest factor was caused by disputes, quarrels, and economic problems. by 7.4%, drunkenness by 2.9%, domestic violence by 0.9%, and polygamy by 0.7%, 3) Divorce in some cases tends to be inconsistent with the teachings of Rasulullah SAW. This type of research is a qualitative research type with a statutory approach, a conceptual approach and a comparative approach. The data collection techniques used in this research are observation, interviews and documentation.